Unhinging the National Framework Perspectives on Transnational Life Writing - Boter, Babs; Rensen, Marleen; Scott-Smith, Giles (CLUES, 2020)
"This book focuses on the 20th century lives of men and women whose life-work and life experiences transgressed and surpassed the national boundaries that existed or emerged in the 20th century. The chapters explore how these life-stories add innovative transnational perspectives to the entangled histories of the world wars, decolonization, the Cold War and post-colonialism. The subjects vary from artists, intellectuals, and politicians to ordinary citizens, each with their own unique set of experiences, interactions and interpretations. They trace the building of socio-cultural and professional networks, the casual encounters of everyday life, and the travel, translation, and preserving of life stories in different media. In these multiple ways the book makes a strong case for reclaiming lost personal narratives that have been passed over by more orthodox nation-state focused approaches. These explorations make use of social and historical categories such as class, gender, religion and race in a transnational context, arguing that the transnational characteristics of these categories overflow the nation-state frame. In this way they can be used to 'unhinge' the primarily national context of history-writing. By drawing on personal records and other primary sources, the chapters in this book release many layers of subjectivity otherwise lost, enabling a richer understanding of how individuals move through, interact with and are affected by the major events of their time. "